The Sagan Effect and Scientists' Public Outreach Participation in China: Multilayered Roles of Social Norms and Rewards. Issue 1 (February 2023) - Chen, Anfan; Zhang, Xing; Jin, Jianbin
In this study, we investigate public outreach participation among Chinese scientists through a multiple mediation model. Factors related to the Sagan effect—negative experiences and negative personal norms—are examined as potential predictors and/or mediators. Based on a national survey of 8, 533 scientists, we validate the Sagan effect triggered by their negative experiences, which indirectly inhibit their outreach participation intentions through negative personal norms. Moreover, positive social norms and rewards play multilayered roles in mitigating the Sagan effect and improving such intentions. This study provides a more comprehensive examination of the underlying mechanisms behind scientists' willingness to engage with the public.